Novel Cell Lines Isolated From Mouse Embryonic Stem Cells Exhibiting De Novo Methylation of the E-Cadherin Promoter. (14th October 2014) - Hawkins, Kate; Keramari, Maria; Soncin, Francesca; Segal, Joe M.; Mohamet, Lisa; Miazga, Natalie; Ritson, Sarah; Bobola, Nicoletta; Merry, Catherine L. R.; Ward, Christopher M.
Abstract : Mouse embryonic stem cells (mESCs) and epiblast stem cells represent the naïve and primed pluripotent states, respectively. These cells self-renew via distinct signaling pathways and can transition between the two states in the presence of appropriate growth factors. Manipulation of signaling pathways has therefore allowed the isolation of novel pluripotent cell types such as Fibroblast growth factor, Activin and BIO-derived stem cells and IESCs. However, the effect of cell seeding density on pluripotency remains unexplored. In this study, we have examined whether mESCs can epigenetically regulate E-cadherin to enter a primed-like state in response to low cell seeding density. We show that low density seeding in the absence of leukaemia inhibitory factor (LIF) induces decreased apoptosis and maintenance of pluripotency via Activin/Nodal, concomitant with loss of E-cadherin, Signal transducer and activator of transcription phosphorylation, and chimera-forming ability. These cells, E-cadherin negative proliferating stem cells (ENPSCs) can be reverted to a naïve phenotype by addition of LIF or forced E-cadherin expression. However, prolonged culture of ENPSCs without LIF leads to methylation of the E-cadherin promoter (ENPSC M ), which cannot be reversed by LIF supplementation, and increased histone H3K27 and decreased H3K4 trimethylation. Transcript analysis of ENPSC M revealed a primed-like phenotype and their differentiation leads to enrichment of neuroectoderm cells. The generation of ENPSCs is similar to tumorigenesis as ENPSCs exhibit transcript alterations associated with neoplasia, hyperplasia, carcinoma, and metastasis. We therefore describe a novel cell model to elucidate the role of E-cadherin in pluripotency and to investigate epigenetic regulation of this gene during mESC differentiation and tumor metastasis. Stem Cells 2014;32:2869–2879